Investigation of CNTFET performance with gate control coefficient effect - Khan, Sabbir Ahmed; Hasan, Md. Rakibul; Mominuzzaman, Sharif Mohammad (© 2014 Sumy State University, 2017)
This article was published in Journal of Nano- and Electronic Physics [© 2014 Sumy State University] The article website is at: http://article.sapub.org/10.5923.j.nn.20140402.03.html